Lower hypoxia thresholds of cuttlefish early life stages living in a warm acidified ocean - Rosa, Rui (The Royal Society, 2013)
The combined effects of future ocean acidification and global warming on the hypoxia thresholds of marine biota are, to date, poorly known. Here, we show that the future warming and acidification scenario led to shorter embryonic periods, lower survival rates and the enhancement of premature hatching in the cuttlefish Sepia officinalis. Routine metabolic rates increased during the embryonic period, but environmental hypercapnia significantly depressed pre-hatchling's energy expenditures rates (independently of temperature). During embryogenesis, there was also a significant rise in the carbon dioxide partial pressure in the perivitelline fluid (PVF), bicarbonate levels, as well as a drop in pH and oxygen partial pressure (pO(2)). The critical partial pressure (i.e. hypoxic threshold) of the pre-hatchlings was significantly higher than the PVF oxygen partial pressure at the warmer and hypercapnic condition. Thus, the record of oxygen tensions below critical pO(2) in such climate scenario indicates that the already harsh conditions inside the egg capsules are expected to be magnified in the years to come, especially in populations at the border of their thermal envelope. Such a scenario promotes untimely hatching and smaller post-hatching body sizes, thus challenging the survival and fitness of early life stages.